Efficacy of dexamethasone in reducing the incidence of postoperative sore throat: a double blind randomized study - Manandhar, Sujita; Manandhar, Kishor; Khakrel, Sharad (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Postoperative sore throat (POST) is a commonly seen adverse event after general anesthesia with endotracheal intubation. Dexamethasone, a potent corticosteroid with anti-inflammatory action is the most popular steroid studied in this regard with positive results. Methods: This randomized, prospective, double-blinded, placebo-controlled study was conducted on one hundred and ten adult patients of either sex, American Society of Anesthesiologists physical status I & II, undergoing elective surgeries requiring endotracheal tube intubation. After obtaining written informed consent, they were randomly divided into Control (A, n=55) and Dexamethasone (B, n=55) groups and received either an injection of Dexamethasone (Group B) 8 mg intravenously or an equivalent volume of Normal Saline (Group A) just before entering the operating theatre. All the patients received a similar anesthesia with endotracheal tube intubation and at the end of surgery, extubated and transferred to the post-anesthesia care unit. The incidence and severity of sore throat were assessed at 1, 6 and 24 hours post-extubation. Severity of sore throat were graded on a 4 point scale, p <0.05 was considered significant. Results: Incidence of POST in Dexamethasone group was found significantly low compared to the control group up to six hours (p<0.05) but was comparable at 24 hours post extubation. Severity of POST in the study group was of lower grade in compare to control group. Conclusions: Prophylactic intravenous Dexamethasone 8 mg administered to patients undergoing elective surgeries requiring endotracheal tube intubation significantly reduces the incidence and severity of POST up to six hours post-extubation.